Effect of mode of urea supplementation on nutrient utilization from straw-based diet by buffalo calves - SINGH, P; KISHAN, JAI (The Indian Journal of Animal Sciences, 2013)
Studies were conducted on 16 growing male buffalo calves in 4 groups of 4 each (average body weight 228 kg) to determine the effect of mode of urea supplementation on nutrient utilization from straw-based diet. Animals in control group were given conventional concentrate mixture with wheat straw as basalroughage. In 3 experimental groups 30% of the protein requirement were met through urea fed either mixed with concentrate mixture (group 2) or wheat straw (group 3) or as urea-ammonia-treated straw (group 4). Urea supplementation in either mode did not improve the dry-matter intake and digestibility of DM, EE, NFE and TCHO. Urea-NH, treatment of straw did improve the digestibility (p